Flavonoids for Allergic Diseases: Present Evidence and Future Perspective - Tanaka, Toshio (Current Pharmaceutical Design, 2014)
The prevalence of allergic diseases has increased worldwide during the past two decades. Change of dietary habit is thought to be one of the environmental factors, which has caused such an increase and worsened allergic symptoms, which suggests that an appropriate dietary habit may substantially prevent the onset of allergic diseases and ameliorate allergic symptoms. Flavonoids, which are polyphenolic plant secondary metabolites ubiquitously present in vegetables, fruits and beverages, possess antioxidant and anti-allergic activities as well as immune-modulating traits. Flavonoids inhibit the activation of mast cells and basophils and therefore suppress the release of chemical mediators, synthesis of Th2 type cytokines such as interleukin (IL)-4 and IL-13, and CD40 ligand expression, They also reportedly inhibit IL-4-induced signal transduction and affect the differentiation process of naïve CD4+ T cells into effector T cell subsets. A cohort epidemiological study in Finland found a significantly low incidence of asthma in a population with a high intake of flavonoids. Moreover, various studies of flavonoids in allergic models such as asthma, atopic dermatitis, anaphylaxis and food allergy demonstrated their beneficial effects, while experience in humans is at the moment limited to respiratory allergy. Although further validation is required, it is anticipated that an appropriate intake of flavonoids may play a role in the prevention and eventually in the management of allergic diseases.
Keywords: asthma